Deep Vein Thrombosis Provoked by Inferior Vena Cava Agenesis - Raad A. Haddad; Mazin Saadaldin; Binay Kumar; Ghassan Bachuwa (Case Reports in Vascular Medicine)
Inferior vena cava agenesis (IVCA) is a rare congenital anomaly that can be asymptomatic or present with vague, nonspecific symptoms, such as abdominal or lower back pain, or deep vein thrombosis (DVT). Here, we present a 55-year-old male who came with painless swelling and redness of his left lower limb. On examination, swelling and redness were noted extending from the left foot to the upper thigh; it was also warm compared to his right lower limb. Venous Doppler ultrasound was done which showed DVT extending up to the common femoral vein. Subsequently, computed-tomography (CT) of the chest and abdomen was done to exclude malignancy or venous flow obstruction; it revealed congenital absence (agenesis) of the infrarenal inferior vena cava (IVC).